2022
DOI: 10.1186/s12888-021-03669-2
|View full text |Cite|
|
Sign up to set email alerts
|

Family-based cognitive behavioural therapy versus family-based relaxation therapy for obsessive-compulsive disorder in children and adolescents: protocol for a randomised clinical trial (the TECTO trial)

Abstract: Background Cognitive behavioural therapy (CBT) is the recommended first-line treatment for children and adolescents with obsessive-compulsive disorder (OCD), but evidence concerning treatment-specific benefits and harms compared with other interventions is limited. Furthermore, high risk-of-bias in most trials prevent firm conclusions regarding the efficacy of CBT. We investigate the benefits and harms of family-based CBT (FCBT) versus family-based psychoeducation and relaxation training (FPRT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…We will include audio recordings from a total of 64 youths aged 8 to 17 years (47 with OCD and 17 healthy controls). The audio recordings of diagnostic interviews stem from a large randomized clinical trial and case-control study of OCD, called TECTO [ 17 ]—TECTO runs at a public hospital in Denmark.…”
Section: Methodsmentioning
confidence: 99%
“…We will include audio recordings from a total of 64 youths aged 8 to 17 years (47 with OCD and 17 healthy controls). The audio recordings of diagnostic interviews stem from a large randomized clinical trial and case-control study of OCD, called TECTO [ 17 ]—TECTO runs at a public hospital in Denmark.…”
Section: Methodsmentioning
confidence: 99%
“…Psychoeducation is one of the available forms; it can be conducted for parents alone or as part of family-based CBT (FCBT) treatment for different purposes, such as increasing parents’ knowledge of mental health, helping create a more supportive family environment, improving their parenting styles and raising parents’ awareness of FA [ 20 ]. Furthermore, FCBT interventions include teaching parents to reduce FA, training them to assist their children with homework and ERP therapy and helping parents identify and cope with the pain and anxiety they feel when facing their child’s OCD [ 145 , 146 , 147 , 148 ]. Studies have shown that these FCBT techniques have similar effects on parents and OCD children [ 145 ].…”
Section: Primary Secondary and Tertiary Prevention Of Pediatric Ocdmentioning
confidence: 99%
“…The interview generally lasts 30 to 90 minutes. We used audio from a randomized clinical trial and case-control study of obsessive-compulsive disorder (OCD), the TECTO trial [7] . Thus, the participants in this cohort included 8-17 year old children with OCD and children with no psychiatric diagnoses.…”
Section: Resource Description 21 Datasetmentioning
confidence: 99%